2018
DOI: 10.1111/dme.13775
|View full text |Cite
|
Sign up to set email alerts
|

Differences in health outcomes associated with initial adherence to oral antidiabetes medications among veterans with uncomplicated Type 2 diabetes: a 5‐year survival analysis

Abstract: People who are non-adherent to treatment were more likely to experience detrimental health outcomes within the first 5 years of antidiabetes therapy. Adherence is paramount to disease management and this should be stressed from the time at which treatment is initiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 27 publications
0
31
0
1
Order By: Relevance
“…telemedicine approaches, including websites and electronic records) [ 58 ]. In addition, the impact of treatment persistence and adherence on disease management must be stressed at the time of treatment initiation [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…telemedicine approaches, including websites and electronic records) [ 58 ]. In addition, the impact of treatment persistence and adherence on disease management must be stressed at the time of treatment initiation [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective database analysis of new OAD users found that good adherence (defined as MPR ≥ 0.8) was associated with significantly reduced risk of a new microvascular or macrovascular diabetes complication (adjusted hazard ratio 0.96; 95% CI 0.92–1.00; P = 0.05) [ 64 ]. Initial adherence appears to be important, with another retrospective cohort study observing that during the first 5 years of OAD treatment, those who were initially nonadherent to therapy were more likely to experience myocardial infarction, ischaemic stroke, or death [ 65 ].…”
Section: Impact Of Treatment Adherence On Clinical and Economic Outcomentioning
confidence: 99%
“…Poor glycaemic control due to non-adherence to OADs can lead to higher microvascular complications (ie, nephropathy, retinopathy, and neuropathy),67 higher macrovascular complications (ie, MI and ischaemic stroke)68 and high risk of mortality,68 hospitalisation and emergency department visits 16. Besides, poor glycaemic control due to non-adherence to OADs can lead to an increased diabetes care cost.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous analyses comparing cardiovascular, cerebrovascular, microvascular, and all-cause mortality outcomes by medication adherence status among veterans with diabetes revealed that while many outcomes were improved by higher rates of medication use, adherence did not prevent all targeted outcomes. 12 Moreover, when adjusting for patient characteristics and first-year medication adherence, differences in outcomes were observed in subgroups of this population, including minorities and those residing in different geographical regions. Such findings reinforce the importance of adherence while suggesting the need for deeper analyses focusing on potential disparities among population subgroups.…”
Section: Introductionmentioning
confidence: 88%
“…In analyses ranging from 3 to 9 years of follow-up, being adherent has been connected with a decreased likelihood of diabetes-related outcomes, such as hypoglycemia, microvascular complications, hospitalization, and cardiovascular or cerebrovascular events. [12][13][14][15][16] Despite comparatively better outcomes by having more medication on hand (i.e., higher PDC), being adherent to antidiabetic medications is not a guarantee that undesired outcomes will be avoided. Our previous analyses comparing cardiovascular, cerebrovascular, microvascular, and all-cause mortality outcomes by medication adherence status among veterans with diabetes revealed that while many outcomes were improved by higher rates of medication use, adherence did not prevent all targeted outcomes.…”
Section: Introductionmentioning
confidence: 99%